Switching Off the Surveillance Society? Legal regulation of CCTV in the UK - Edwards, Lilian (Asser Press, 2005)
The article discusses the prevalence of CCTV (close circuit television) specifically in Britain, as one of the most watched societies in Europe. The notion of "the surveillance society" and subsequent invasion of privacy is contrasted with its counter argument, of CCTV as a means of reducing crime. Questions, not merely whether CCTV should be regulated, but the extent of regulation, are highlighted in attempts to assess the appropriate balance to be met.
Keywords: CCTV; surveillance society